2015
DOI: 10.1111/acem.12835
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to an Accelerated Diagnostic Protocol for Chest Pain: Secondary Analysis of the HEART Pathway Randomized Trial

Abstract: Objectives Accelerated diagnostic protocols (ADP), such as the HEART Pathway, are gaining popularity in emergency departments (EDs) as tools used to risk-stratify patients with acute chest pain. However, provider non-adherence may threaten the safety and effectiveness of ADPs. The objective of this study was to determine the frequency and impact of ADP non-adherence. Methods A secondary analysis of participants enrolled in the HEART Pathway RCT was conducted. This trial enrolled 282 adult ED patients with sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…A recent randomized trial showed that, compared to usual care, use of the HEART Pathway increased early discharges by 21.3%, decreased length of stay in the hospital by 12 hours, and decreased objective cardiac testing at 30 days by 12.0% without increasing adverse events. 15,16 The use of the HEART Pathway as a decision aid for patients with undifferentiated chest pain has also shown a significant cost savings. 17 The prehospital arena is a natural extension of this work due to the large number of patients that present to the ED via ambulance.…”
Section: Discussionmentioning
confidence: 99%
“…A recent randomized trial showed that, compared to usual care, use of the HEART Pathway increased early discharges by 21.3%, decreased length of stay in the hospital by 12 hours, and decreased objective cardiac testing at 30 days by 12.0% without increasing adverse events. 15,16 The use of the HEART Pathway as a decision aid for patients with undifferentiated chest pain has also shown a significant cost savings. 17 The prehospital arena is a natural extension of this work due to the large number of patients that present to the ED via ambulance.…”
Section: Discussionmentioning
confidence: 99%
“…While the ADAPT accelerated diagnostic protocol (ADP) identified 20% of patients as low risk in clinical practice, most (79%) underwent further outpatient investigations for coronary artery disease 23 . A small randomised trial of the HEART pathway (282 participants) found a 21% increase in early discharges, and objective testing of low risk patients was reduced by 12%; 24 non‐adherence by providers to the HEART pathway affected 20% of patients 25 . A randomised study of the EDACS and ADAPT ADPs found that 41.6% and 30.5% of patients (respectively) were at low risk, but continued to recommend early investigation in an ambulatory setting because of the observational nature of the original trials 18 .…”
Section: Discussionmentioning
confidence: 99%
“…23 A small randomised trial of the HEART pathway (282 participants) found a 21% increase in early discharges, and objective testing of low risk patients was reduced by 12%; 24 nonadherence by providers to the HEART pathway affected 20% of patients. 25 A randomised study of the EDACS and ADAPT ADPs found that 41.6% and 30.5% of patients (respectively) were at low risk, but continued to recommend early investigation in an ambulatory setting because of the observational nature of the original trials. 18 Similar to IMPACT, these ADPs apply early troponin testing (0 and 2 hours for EDACS and ADAPT; 0 and 3 hours for HEART) and a risk stratification score (EDACS, Thrombolysis In Myocardial Infarction [TIMI], or HEART) to identify low risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our nonadherence rate was even higher than those reported in other recent investigations, which also show providers tend to be more conservative with diagnostic ordering without clinical benefit in the low-risk cohort as defined by the HEART score. 15 …”
Section: Discussionmentioning
confidence: 99%